The Effects of Health Information Technology Change Over Time: A Study of Tele-ICU Functions - Anders, S.H.; Woods, D.D.; Schweikhart, S.; Ebright, P.; Patterson, E. (Applied Clinical Informatics, 2012)
Objective: Longitudinal studies exploring the evolution of health information technology functions provide valuable information about how technology systems are integrated and exploited in situ. This study reports changes in the distribution of functions for a specific health information technology, the tele-ICU, over time. The studied tele-ICU provided care to six remote ICUs within a local geographic region in the same state and had nursing staff around the clock.Methods: The intervention logs of tele-ICU nurses were collected during two discrete times and coded into nine emergent functional categories, who initiated the intervention and, if required, subsequent escalation. All coded functional categories were investigated for significant changes over time in the nursing logged interventions.Results: A total of 1927 interventions were coded into the nine emergent functional categories. Seven of the nine categories (78%) were significantly different between 2005 and 2007. The functions of the tele-ICU system continue to change and develop over time.Conclusion: These findings suggest that the tele-ICU increased support when ICU nurses were off the unit, inter-hospital coordinating and adherence to best practices, while simultaneously decreasing real-time support for ICU nurses. This research suggests that sustaining safety features in a new technology over time have post-conditions after implementation.
Keywords: Medical informatics applications; telemedicine; patient care; intensive care